2020
DOI: 10.1021/acscentsci.9b00743
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Living Bacteria in Vivo Using d-Alanine-Derived 11C Radiotracers

Abstract: Incorporation of D-amino acids into peptidoglycan is a unique metabolic feature of bacteria. Since D-amino acids are not metabolic substrates in most mammalian tissues, this difference can be exploited to detect living bacteria in vivo. Given the prevalence of D-alanine in peptidoglycan muropeptides, as well as its role in several antibiotic mechanisms, we targeted this amino acid for positron emission tomography (PET) radiotracer development. D-[3-11 C]Alanine and the dipeptide D-[3-11 C]alanyl-Dalanine were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(114 citation statements)
references
References 48 publications
3
110
1
Order By: Relevance
“…With metabolic products being consistently observed, hyperpolarized d ‐[1‐ 13 C]alanine can be employed to rapidly assess DAO activity in vitro and in vivo . When compared to other molecular imaging techniques that exploit d ‐amino acids, the main ones being PET with d ‐[methyl‐ 11 C]methionine and d ‐[3‐ 11 C]alanine as a contrast agent for bacterial infection, hyperpolarized d ‐alanine shows greater specificity for detecting DAO activity.…”
Section: Discussionmentioning
confidence: 99%
“…With metabolic products being consistently observed, hyperpolarized d ‐[1‐ 13 C]alanine can be employed to rapidly assess DAO activity in vitro and in vivo . When compared to other molecular imaging techniques that exploit d ‐amino acids, the main ones being PET with d ‐[methyl‐ 11 C]methionine and d ‐[3‐ 11 C]alanine as a contrast agent for bacterial infection, hyperpolarized d ‐alanine shows greater specificity for detecting DAO activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recently published paper by Parker et al showed a 3.5-fold higher accumulation of 11 C-D-ala in a mouse model of acute bacterial myositis compared with the sterile inflammation control, whereas 68 Ga-citrate showed only 2-fold higher accumulation in the same model. Furthermore, in a vertebral diskitis-osteomyelitis modal, 11 C-D-ala showed a 3.3-fold higher uptake than in adjacent disk spaces and a 1.8-fold uptake in P. aeruginosa pneumonia relative to normal lung ( Figure 5C) (73).…”
Section: D-amino Acidsmentioning
confidence: 96%
“…The polymyxin B is an antibiotic, usually used for multidrug-resistant Gram-negative bacteria, that acts like an amphipathic antimicrobial peptide. Similarly, D-amino acids, molecules targeting the folate pathway in bacteria and siderophores have also been studied as bacterial specific imaging agents [34][35][36][37][38][39].…”
Section: Imaging Bacteria In Animal Modelsmentioning
confidence: 99%